Capacity Development for Internal and External Auditors in the Complex Adaptive System of Higher Education in Vietnam - Kemenade, Everard (Vietnam Journal of Education, 2021)
The question answered in this paper is: What is needed in the complex adaptive system of higher education to make Vietnamese professionals more receptive to internal and external reviews and how can we achieve that? The purpose is to magnify the effects of an accreditation system in general and those of the audits or reviews in particular. The findings are gathered through a dynamic orientation in scientific literature using the berry-picking method (Bates, 1989). The results - regarding the development of quality management in Viet Nam in general and accreditation specifically- have been analyzed using the four paradigms of quality management. The accreditation reviews in higher education would be more effective, if the interviewees were more open to show their organizations’ strengths and weaknesses instead of withdrawing from the survey and performing dramaturgical compliance. Thus, an appropriate auditor attitude is essential, seven of which are presented in this paper and hopefully to be of critical values to the development of the Vietnamese audit process. Suggestions are proposed concerning how such a development could be achieved using the emergence paradigm.